Selective staining on non-volatile memory cells for data retrieval - Zeng, Xiaomei (2023)
A new data retrieval approach utilizing selective staining is explored to differentiate '0' from '1' cells in EEPROM and Flash memory with node sizes of 40 nm and 250 nm. A two-step staining process based on selective oxide etching and copper galvanic displacement deposition is introduced. The underlying mechanism is attributed to the difference in electric field across the tunnel oxide, which originates from the presence or absence of charges stored in the floating gates. With proper sample preparation, the selectively stained and non-stained cells can be characterized with optical microscopy and scanning electron microscopy, to facilitate direct read-out of data in a time-efficient manner. The physical layout of individual memory cells with respect to the stored data is identified. A systematic data retrieval is achieved with an accuracy of 95% at individual bit level. This selective staining technique marks the data permanently on the chip that allows for subsequent analysis and evidence retention.